A novel tissue specific alternative splicing variant mitigates phenotypes in Ets2 frame-shift mutant models - Yuki Kishimoto (Nature Portfolio, 2021)
Abstract E26 avian leukemia oncogene 2, 3′ domain (Ets2) has been implicated in various biological processes. An Ets2 mutant model (Ets2 db1/db1 ), which lacks the DNA-binding domain, was previously reported to exhibit embryonic lethality caused by a trophoblast abnormality. This phenotype could be rescued by tetraploid complementation, resulting in pups with wavy hair and curly whiskers. Here, we generated new Ets2 mutant models with a frame-shift mutation in exon 8 using the CRISPR/Cas9 method. Homozygous mutants could not be obtained by natural mating as embryonic development stopped before E8.5, as previously reported. When we rescued them by tetraploid complementation, these mice did not exhibit wavy hair or curly whisker phenotypes. Our newly generated mice exhibited exon 8 skipping, which led to in-frame mutant mRNA expression in the skin and thymus but not in E7.5 Ets2 em1/em1 embryos. This exon 8-skipped Ets2 mRNA was translated into protein, suggesting that this Ets2 mutant protein complemented the Ets2 function in the skin. Our data implies that novel splicing variants incidentally generated after genome editing may complicate the phenotypic analysis but may also give insight into the new mechanisms related to biological gene functions.